Peer-teaching in the food chemistry laboratory: student-produced experiments, peer and audio feedback, and integration of employability skills - Julie L. Dunne (International Journal of Food Studies)
This paper describes the author’s experience over the last several years of implementing an alternative Food Chemistry laboratory practical model for a group of third-year BSc Nutraceuticals students. The initial main objectives were to prepare students for the more independent final-year research project; to incorporate innovative approaches to feedback; and to integrate key employability skills into the curriculum. These were achieved through building the skills required to ultimately allow students working in groups to research, design and run a laboratory for their class. The first year of the project involved innovative approaches to feedback, including weekly feedback sessions, report checklists and audio feedback podcasts. Student evaluation after one year suggested the case group felt more prepared for final-year research projects and work placement owing to the redesign of the laboratory assessment. This, together with general positive feedback across several indicators, was proof of concept, and was a foundation for an improved model. The improvements related to the organisation and management of the project, but the same pedagogical approach has been retained. The second year saw the introduction of a more rigorous and easier to manage peer evaluation through use of the online Comprehensive Assessment for Team-Member Effectiveness (CATME) tool. The most recent revision has included a Project Wiki hosted on Blackboard™to facilitate the organisation, communication, assessment and feedback of student-generated resources. More recently, the final-year students who had participated in the peer-teaching Food Chemistry labs when in third year have been evaluated. This evaluation took place following their research projects, and suggests that the peer-teaching model better prepared them for these activities, compared to traditional laboratories.